2021
DOI: 10.4314/ijbcs.v15i3.24
|View full text |Cite
|
Sign up to set email alerts
|

Production et gestion des huiles usées de la ville de Ouagadougou, Burkina Faso

Abstract: La production des déchets est inhérente aux activités humaines, qu’elles soient domestiques, agricoles, industrielles ou commerciales. A la faveur d’une urbanisation galopante et de ses corollaires, l’assainissement et la gestion des déchets sont devenus des préoccupations importantes. Si la situation de déchets ménagers semble connaître une évolution dans la capitale burkinabé, ce n’est pas le cas pour les déchets des industries et des transports comme les huiles usées. Ce travail avait pour objectif d’étudie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…This can promote an increase in the number of microorganisms in the environment, leading to an accumulation of soil organic matter in the tree rooting zone compared with open areas [20]. Indeed, studies have reported that Guiera senegalensis and Piliostigma reticulatum have been identified to promote fungi, microbial diversity and litter decomposition [5]. The presence of micro-organisms in the tree rooting zone is due in part to the fact that phosphorus, an essential ecosystem element, is not present in the soil [21,22].…”
Section: Cob Grain and Stover Yields By Production Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…This can promote an increase in the number of microorganisms in the environment, leading to an accumulation of soil organic matter in the tree rooting zone compared with open areas [20]. Indeed, studies have reported that Guiera senegalensis and Piliostigma reticulatum have been identified to promote fungi, microbial diversity and litter decomposition [5]. The presence of micro-organisms in the tree rooting zone is due in part to the fact that phosphorus, an essential ecosystem element, is not present in the soil [21,22].…”
Section: Cob Grain and Stover Yields By Production Systemmentioning
confidence: 99%
“…Indeed, the choice of species, their density and their arrangement in cultivated plots depend on the socio-economic and ecological benefits they bring to the population. Most farmers in the semi-arid zones of West Africa consider trees to be an integral part of the production system [4,5]. Worldwide, studies on these combinations have attracted the attention of many scientists.…”
Section: Introductionmentioning
confidence: 99%
“…In order to prevent these negative effects, environmental protection must be integrated into the project as soon as possible. This is also justified by Law No.006-2013/AN on the Environment Code in Burkina Faso, which stipulates in article 25 that any activity likely to have significant environmental impacts is subject to an environmental impact study or notice (Yelemou & al., 2021). Action 2: Drainage or cleaning of water bodies.…”
Section: Identification Of Potential Actions To Combat Degradationmentioning
confidence: 99%